Racialization, Racism, and Anti-Racism in the Nordic Countries - Hervik, Peter; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book represents a comprehensive effort to understand discrimination, racialization, racism, Islamophobia, anti-racist activism, and the inclusion and exclusion of minorities in Nordic countries. Examining critical media events in this heavily mediatized society, the contributors explore how processes of racialization take place in an environment dominated by commercial interests, anti-migrant and anti-Muslim narratives and sentiments, and a surprising lack of informed research on national racism and racialization. Overall, in tracing how these individual events further racial inequalities through emotional and affective engagement, the book seeks to define the trajectory of modern racism in Scandinavia. .
1. Introduction: Racialization in the Nordic Countries: An Introduction -- 2. Racial Turns and Returns: Discrediting Danish Research on Racism in Public Media Debates -- 3. Racialized Rape and the Politics of Fear: Intersectional Reading of the Kempele Rape Case -- 4. Identity Constructions of Muslims in Western News Media -- 5. White Fear: The Fantasy of a White Fearing Public as Catalyst for the Racialization of Terror in Television News -- 6. Justification and Rationalization of Attitudes Toward Interracial Relationships in Color-blind Sweden -- 7. The Proliferation of 'Entitlement Racism': A Study of Denials and Trivialization of Racism and Discrimination in Danish Public Discourse -- 8. Racialization in Humanitarianism: Conditionality of Suitable Victims in Asylum Seekers' Protests -- 9. Do Antiracist Efforts and Diversity Programs Make a Difference? Assessing the Case of Norway -- 10. Communicating Anti-Racism: Social Movements, Non-profit Organizations and their Mediated Claims-Making in Finland and Sweden -- 11. (Re)Framing Racialization: Djurs Sommerland as a Battleground of (Anti)Racism -- 12. Resisting/Resistant Islamophobia: Norway and the Securitization of Muslims in the Post 22/7 2011 Era -- 13. Conclusions.
Keywords: Race; Sex; Culture; Communication; Emigration and immigration; Race and Ethnicity Studies; Gender Studies; Sociology of Culture; Media and Communication; Human Migration